2016
DOI: 10.3389/fimmu.2016.00051
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow T Cells and the Integrated Functions of Recirculating and Tissue-Resident Memory T Cells

Abstract: Changes in T cell trafficking accompany the naive to memory T cell antigen-driven differentiation, which remains an incompletely defined developmental step. Upon priming, each naive T cell encounters essential signals – i.e., antigen, co-stimuli and cytokines – in a secondary lymphoid organ; nevertheless, its daughter effector and memory T cells recirculate and receive further signals during their migration through various lymphoid and non-lymphoid organs. These additional signals from tissue microenvironments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 167 publications
2
80
0
Order By: Relevance
“…In fact, there is ample evidence for continuous migration of CD8 + T cells to and from the BM over longer periods of time [28,38]. This rather suggests that CD8 + T cells use perivascular niches in the BM as a temporary stopping point before they migrate elsewhere [38]. In conjunction with the findings by Chaix et al [20], we postulate that CXCR4 may be essential for homeostatic proliferation and/or maintenance of CD8 + T cells, as it guides these cells toward specialized CXCL12 high stromal niches, which we found to be rich in the supporting cytokines IL-7 and IL-15.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is ample evidence for continuous migration of CD8 + T cells to and from the BM over longer periods of time [28,38]. This rather suggests that CD8 + T cells use perivascular niches in the BM as a temporary stopping point before they migrate elsewhere [38]. In conjunction with the findings by Chaix et al [20], we postulate that CXCR4 may be essential for homeostatic proliferation and/or maintenance of CD8 + T cells, as it guides these cells toward specialized CXCL12 high stromal niches, which we found to be rich in the supporting cytokines IL-7 and IL-15.…”
Section: Discussionmentioning
confidence: 99%
“…Where the antigen‐experienced T cells of the circulating memory obtain the signals to proliferate, die, or exit a particular tissue is unclear. It has been discussed that the bone marrow may provide a hub for circulating memory T lymphocytes 103. IL‐7‐expressing cells are abundant also in the gut and in the lymphoid organs104 as are professional antigen‐presenting cells 105, 106…”
Section: The Lifestyle Of Circulating Memory T Lymphocytesmentioning
confidence: 99%
“…Feeding mice with BrdU resulted in a marked increase in Ki‐67 + CD8 + memory T cells, and cells in S/G2/M phases of cell cycle, according to staining of their DNA with propidium iodide. This was even more prominent for memory CD8 + T cells of bone marrow, a finding which led to an ongoing debate on the nature and lifestyle of memory T cells in the bone marrow 103, 118, 119, 120, 121, 122, 123, 124…”
Section: The Bone Marrow—hub For Circulating or Home Of Resident Memomentioning
confidence: 99%
“…In addition to CD8 + T RM cells, resting memory CD4 + T cells in the BM require CD69 expression for their recruitment and maintenance in BM (Table ). It has been reported that, in an immune response, memory T cells preferentially reside and rest on stromal niches of the BM, suggesting that the BM works as a “reservoir” for long‐lived memory T cells .…”
Section: Roles Of Cd69 Expression In Trm Cells and Bm Memory T Cellsmentioning
confidence: 99%
“…In addition to CD8 + T RM cells, resting memory CD4 + T cells in the BM require CD69 expression for their recruitment and maintenance in BM (Table ). It has been reported that, in an immune response, memory T cells preferentially reside and rest on stromal niches of the BM, suggesting that the BM works as a “reservoir” for long‐lived memory T cells . Because we identified Myl9 in BM lysates as a CD69 ligand by pull‐down assay using the murine CD69 extracellular domain, it is likely that the CD69‐Myl9 system may also work in the recruitment and maintenance of memory CD4 T cells in the BM, although Myl9‐expressing cells to recruit CD69 + cells into the BM should be identified.…”
Section: Roles Of Cd69 Expression In Trm Cells and Bm Memory T Cellsmentioning
confidence: 99%